1994
DOI: 10.2307/3578913
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Prenatal Ultrasound Exposure on Postnatal Growth and Acquisition of Reflexes

Abstract: The examination of pregnant women using diagnostic ultrasound has increased greatly over past decades in the United States. As sonography techniques have been altered and refined, there has been renewed interest concerning possible effects on the developing fetus, since exposures in mid-gestation occur during the sensitive period of brain development. The present study is concerned with possible neonatal functional deficits due to exposure of the fetus to ultrasound. An ultrasound exposure tank was designed sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Postnatal weights of female and male offspring were monitored weekly for 20 weeks and were published previously. There were no significant dose-related alterations in postnatal weight or postnatal growth rates (18). Adult behavioral tests were initiated on postnatal Day 60.…”
Section: Methodsmentioning
confidence: 99%
“…Postnatal weights of female and male offspring were monitored weekly for 20 weeks and were published previously. There were no significant dose-related alterations in postnatal weight or postnatal growth rates (18). Adult behavioral tests were initiated on postnatal Day 60.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental efforts to delineate the biological effects of ultrasound on in utero development have been inconclusive. Some studies have reported increased malformation rates (Stolzenberg et al, 1980a;Saravazayan et al, 1982;Takabayashi et al, 1985), while others have found no such effects (Kimmel et al, 1983(Kimmel et al, , 1989Gates, 1984, 1985;Child et al, 1984Child et al, , 1989Vorhees et al, 1991;Jensh et al, 1994). Furthermore, there are conflicting reports concerning the effects of ultrasound exposure on body weight and behavioral changes (Stewart et al, 1985;Hendrickx, 1989a, 1989b;Norton et al, 1991;Hande and Uma Devi, 1992, 1993Newnham et al, 1993;Vorhees et al, 1994;Uma Devi et al, 1995;Fisher et al, 1996;Suresh et al, 1996).…”
Section: Introductionmentioning
confidence: 99%